Quantitative effects of changes in agricultural irrigation on potential evaporation. Issue 2 (23rd February 2021) - Han, Congying; Zhang, Baozhong; Han, Songjun
Abstract: Evaporation is a key element to the basin's water cycle. Agricultural irrigation has resulted in a significant variation of regional potential evaporation ( E pen ). The spatiotemporal variation of E pen and influencing factors in natural, agricultural, and desert areas in different developmental stages of irrigation in Heihe River Basin (HRB) from 1970 to 2017 were comparatively analysed in this study. This work focused on the correction effect of irrigation on the variation of E pen . Agricultural water consumption in HRB significantly varied around 1998 due to agricultural development and water policy. Under the influence of irrigation, annual variations of E pen in agricultural, natural, and desert areas were significantly different. From 1970 to 1998, the annual trend slope of E pen in natural area only reduced by 1 mm decade −1, while that in agricultural area significantly decreased by 39 mm decade −1 . After the implementation of water‐saving irrigation, E pen in natural and agricultural areas increased by 11 and 54 mm decade −1, respectively, from 1998 to 2017. In contrast with natural and agricultural areas, E pen in desert area decreased by 80 mm decade −1 from 1970 to 1998 and continuously decreased by 41 mm decade −1 from 1998 to 2017. However, the regulatory effect of irrigation on E pen in desert area started to manifest due to the expansion of cultivated land area from 2010 to 2017. Irrigation had a significant regulatory effect on the variation of E pen in HRB. The regulatory effect was mainly reflected on the aerodynamic term ( E aero ). Results indicated that the main meteorological factors influencing E pen in each region were wind speed, which is 2 m above the surface ( U 2 ), and water vapour deficit (VPD). Abstract : Distribution of trend slopes per decade of E pen, E rad, and E aero in the different stations in the HRB (1970–2017). Under the influence of irrigation, the annual variation of E pen in the agricultural, natural, and desert areas was significantly different. From 1970 to 1998, the annual trend slope of E pen in the agricultural area significantly decreased by 39 mm decade −1 . After the implementation of water‐saving irrigation, the E pen in the agricultural areas increased by 54 mm decade −1 from 1998 to 2017. The main meteorological factors influencing the variation of E pen in HRB are U 2 and VPD.